2022
DOI: 10.2298/vsp210126039j
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 therapy activates tumoricidic properties of NKT cells and contributes to the overall deceleration of tumor progression in a model of murine mammary carcinoma

Abstract: Introduction: Immune checkpoint therapy is well- established therapeutic approach in treatment of malignant disease and is thought to be mostly based on facilitating adaptive immune responses. However, cells of innate immune response, such as NKT cells, might also be important for successful anti-programmed cell death protein 1 therapy, as they initiate anti-tumor immune response. Materials and methods: For tumor induction, 4T1 cells syngenic to BALB/c background were used after which mice u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…α-PD-1 therapy has shown to invigorate bacteria clearance, but it also suggests that KCs may have impaired tolerogenic function to self-antigens reactive T cells. NKT cells also responded to α-PD-1 therapy and exert increased anti-tumor functions by secretion of IFN- γ secretion of inflammatory cytokines ( 205 ).…”
Section: Immunotherapy-associated Liver Reactionsmentioning
confidence: 99%
“…α-PD-1 therapy has shown to invigorate bacteria clearance, but it also suggests that KCs may have impaired tolerogenic function to self-antigens reactive T cells. NKT cells also responded to α-PD-1 therapy and exert increased anti-tumor functions by secretion of IFN- γ secretion of inflammatory cytokines ( 205 ).…”
Section: Immunotherapy-associated Liver Reactionsmentioning
confidence: 99%
“…One of the ways in which metformin influences immune responses to cancer is by modulating the expression of the programmed death ligand (PD-L1, also known as CD274 or B7-H1) (60). Studies have shown that molecule PD-L1 is expressed at significantly higher levels in various cancer types in which it promotes cell proliferation, migration and invasion while the other studies showed that PD-1 can have immunomodulatory effect (61)(62)(63)(64). Role of PD-L1 is to provide an inhibitory signal to cytotoxic T lymphocytes (CTLs) through binding to an inhibitory PD-1 receptors on activated CTLs.…”
Section: Immunomodulatory Effects Of Metforminmentioning
confidence: 99%